Exploring healthcare system adaptive techniques and challenges in caring for people living with HIV and AIDS during the COVID-19 lockdown period in Harare, Zimbabwe - Tendai Makwara; Rumbidzai Chireshe; Mathew Nyashanu (PAGEPress Publications, 2023)
The COVID-19 pandemic caused unprecedented challenges for healthcare systems worldwide, affecting the provision of ongoing care for people living with HIV and AIDS (PLWHA). This study aimed to explore the adaptive techniques employed by healthcare systems in providing care for PLWHA during the pandemic and the challenges encountered. An exploratory qualitative study (EQS) methodology was employed, underpinned by the resourcefulness framework. The Silences Framework Analysis Phases were used during data analysis. Fifteen participants were interviewed, and the data were thematically analyzed. The healthcare system employed several adaptive techniques to cater to PLWHA during the pandemic, including developing new standard service protocols, implementing preventative measures to limit COVID- 19 infections during hospital visits, and improving communication. The study identified two significant challenges: a lack of health insurance and a shortage of personal protective equipment (PPEs). The findings highlight the need for adapting to changing circumstances and provide ongoing care for PLWHA during the pandemic. The results show that developing new protocols and preventative measures can effectively ensure the continuity of care in pandemic situations. Moreover, the provision of PPEs and health insurance for healthcare staff should be prioritized to create a safe working environment. In conclusion, this study underlined the importance of resourcefulness in developing healthcare resilience to sustain care and support for PLWHA during the COVID-19 pandemic.